EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA SLEMAN - Fika Wahyuningtyas; Alia Ariesanti (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2014)
Tax collection by using a letter of reprimand and forced letter is an effort to increase the effectiveness of tax revenue that purpose as the country's development. This research method aims to determine the level of effectiveness of the tax collection and forced letter warning letter. The research method uses descriptive method of analysis, methods based on existing data, and then draw conclusions. This study uses secondary limit the period 2011-2012. Analysis using ratio analysis to calculate the effectiveness of tax collection by using related variables that include the amount of the tax billing plan and the amount of tax revenue. The results showed that the effectiveness of tax collection with a letter of reprimand and a letter run ineffectively enforced, so expect authorize agencies in collecting tax debts can be optimized, see realize taxes are still very small